(untitled) (Educational Knowledge, 2024)
The formulation of a National Qualifications Framework for Education Careers emerged as a strategic response to a pressing educational challenge within the Costa Rican context. The principal objective of this framework is to catalyze harmonization and educational mobility. The impetus for this initiative was driven by an Interinstitutional Project Management Commission, comprising 9 institutions intricately linked to the Costa Rican educational landscape, alongside their respective technical teams (ET). The design and implementation of the Nacional Framework followed a meticulously crafted roadmap, encompassing the intricacies of methodological development for the construction of Learning Outcomes. The latent objective underlying the Nacional Framework is to function as a discerning instrument, meticulously describing Learning Outcomes to facilitate formative harmonization within the realm of education careers. Through such precision, the endeavor seeks to elevate the quality of prospective professionals by ensuring the concordance, relevance, transparency, comparability, and coherence of university curricula.